How Well Can We Assess Our Ability to Understand Others’ Feelings? Beliefs About Taking Others’ Perspectives and Actual Understanding of Others’ Emotions - Israelashvili, Jacob; Sauter, Disa; Fischer, Agneta (Frontiers in Psychology, 2019)
People vary in their beliefs about their tendency to engage in perspective taking and to understand other’s feelings. Often, however, those beliefs are suggested to be poor indicators of actual skills and thus provide an inaccurate reflection of performance. Few studies, however, have examined whether people’s beliefs accurately predict their performance on emotion recognition tasks using dynamic or spontaneous emotional expressions We report six studies (N range from 186 to 315; N total = 1347) testing whether individuals’ report of their engagement in perspective taking, as measured by the Interpersonal Reactivity Index (IRI; Davis, 1983), is associated with accurate emotion recognition. In Studies 1-3, emotion recognition performance was assessed using three standard tests of nonverbal emotion recognition. To provide a more naturalistic test, we then assessed performance with a new emotion recognition test in Studies 4-6, using videos of real targets that share their emotional experiences. Participants’ multi-scalar ratings of the targets’ emotions were compared with the targets’ own emotion ratings. Across all studies, we found a modest, yet significant positive relationship: people who believe that they take the other’s perspective also perform better in tests of emotion recognition (r = .20, p < .001). Beliefs about taking others’ perspective thus reflect interpersonal reality, but only partially.